2003
DOI: 10.1002/lsm.10156
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary biocompatibility experiment of polymer films for laser‐assisted tissue welding

Abstract: The polymer film was well tolerated by the tissue, and the tissue response to the material was consistent with that seen in the literature. The breaking strength differences between control and film-implanted specimens at 0 and 14 days were probably the result of mechanical complications (tissue apposition and wound contraction) due to the presence of the film, and not due to the film material itself. The use of polymer film patches for liquid solder reinforcement and breaking strength enhancement may have cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…During the last 40 years a focus in research was put on sutureless tissue fusion, to handle the limits of conventional suturing such as vascular wall damage due to the penetrating needle, intraluminal foreign body reactions caused by non-absorbable suture material and thrombocyte aggregation, impaired endothelial function, intimal hyperplasia and hence stenosis [1][2][3][4][5][6]. Sutured wounds have greater and longer duration inflammatory response than laser soldered wounds [7,8]. Furthermore suturing does not create a watertight connection, which can, for example, in visceral surgery lead to an entry for pathogens resulting in severe complications such as infections or death [9].…”
Section: Introductionmentioning
confidence: 99%
“…During the last 40 years a focus in research was put on sutureless tissue fusion, to handle the limits of conventional suturing such as vascular wall damage due to the penetrating needle, intraluminal foreign body reactions caused by non-absorbable suture material and thrombocyte aggregation, impaired endothelial function, intimal hyperplasia and hence stenosis [1][2][3][4][5][6]. Sutured wounds have greater and longer duration inflammatory response than laser soldered wounds [7,8]. Furthermore suturing does not create a watertight connection, which can, for example, in visceral surgery lead to an entry for pathogens resulting in severe complications such as infections or death [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers such as polyglycolic acid or polycaprolactone have been used as carrier material for the liquid solder. They prevent runaway of the liquid solder and give additional strength to the anastomosis [13,[18][19][20][21].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Laser-soldered anastomoses form an immediate watertight connection. Furthermore, it has been shown that laser-soldered wounds have a better inflammatory response than sutured wounds [12][13][14]. As the laser light can be delivered via optical fibers through a catheter, the anastomosis can be performed in a minimally invasive way [15][16][17].…”
Section: Biophotonicsmentioning
confidence: 99%
“…28 Once the solder is irradiated, heating denaturates the solder and the adjacent tissue, which leads to a strong tissue bond. [29][30][31] It has been shown that impregnating a carrier material, such as biocompatible polymer scaffolds, in the solder further improves the results. 31,32 Polycaprolactone (PCL), which was used in this study, has shown favorable soldering results in vascular LTS.…”
mentioning
confidence: 99%
“…[29][30][31] It has been shown that impregnating a carrier material, such as biocompatible polymer scaffolds, in the solder further improves the results. 31,32 Polycaprolactone (PCL), which was used in this study, has shown favorable soldering results in vascular LTS. 23 We designed a plug-shaped, PCL-based solder carrier that can be soldered into the gastric incision and onto the mucosa.…”
mentioning
confidence: 99%